Teacher and Student Capital in Addressing Social Inequality - Dwi, Putri; Inayah, Nur’aini; Kartika Hanindraputri, Eufrasia; Syaifullah, Khalid (Ittishal Educational Research Journal, 2024)
Social inequality in the field of education impacts the implementation of educational goals, causing them to be less than optimal. Education should be accessible to all members of society. The changes occurring in the educational sector require all actors to adapt and follow these changes. This study aims to identify and analyze the strategies employed by teachers and students in addressing social inequality in education during the Covid-19 pandemic. The research utilizes a qualitative research method with a phenomenological approach. A phenomenological approach was chosen in this research to reveal and understand the phenomenon of gaps in education by teachers and students as well as the strategies used by teachers and students in dealing with these gaps. Data collection techniques include in-depth interviews, documentation, and the use of previous studies as references for this research. The collected data were analyzed using Pierre Bourdieu's theory of capital. The results of this study indicate that social inequality in education during the Covid-19 pandemic was driven by the unpreparedness of teachers and students to implement distance learning. However, teachers and students were able to overcome social inequality in education by utilizing the capital they possess, namely social capital, cultural capital, economic capital, and symbolic capital.